(untitled) (International journal of medical sciences, 2025)
Acute leukemia (AL) is a hematologic neoplasm characterized by excessive proliferation of undifferentiated blast cells in the bone marrow and peripheral blood. Understanding the relationship between laboratory and clinical manifestations of the disease is crucial for assessing prognosis, selecting treatment strategies, and evaluating therapeutic response. This article analyzes the clinical significance of hematologic parameters, immunophenotypic markers, cytogenetic, and molecular alterations in patients with AL, based on scientific studies published between 2020 and 2025.